Analisis produksi budidaya nilam di Kecamatan Kulisusu Barat Kabupaten Buton Utara - Legi Muliadi; Bahari Bahari; Muhammad Aswar Limi (Universitas Halu Oleo, 2023)
This research aims to: determine the factors that influence patchouli production, and analyze the relationship between the amount of production and the quality and price of patchouli oil in West Kulisusu District, North Buton Regency. The research was carried out from March to April 2022. The research population was 40 patchouli farmers and 5 patchouli oil refining business owners. The data collected includes: use of production inputs (land area, seeds, fertilizer and labor), quantity and quality of production, and price of patchouli. Data analysis was carried out using the Cobb-Douglas production function and chi-square. The results of the research show that: the production factor that has a real influence on patchouli production is the number of seeds, while the production factors that have an insignificant influence are land area, amount of fertilizer and labor. There is no real relationship between the amount of patchouli production and the quality of patchouli oil, while there is a real relationship between the amount of production and the price of patchouli oil. Key words: production; processing; patchouli oil